Merek, Kualitas, Dan Harga Sebagai Dasar Pengambilan Keputusan Pembelian Honda Beat - Susiani Susiani (BIP's JURNAL BISNIS PERSPEKTIF, 2019)
The purpose of this study is to find out and analyze the influence of brand, quality,and price on consumer decisions in buying Honda Beat in North Surabaya. Thepopulation in this study were all Honda Beat buyers in North Surabaya. Samplingis done accidental sampling, with the number of sample members of 100respondents. The analytical method used in this study is the method of analysis ofMultiple Linear Regression. The results of the analysis show that the brand,quality, and price both simultaneously and partially have a significant effect onHonda Beat purchasing decisions. The price variable is the independent variablethat has the dominant influence on Honda Beat purchasing decisions.